2007
DOI: 10.1002/eqe.692
|View full text |Cite
|
Sign up to set email alerts
|

Response of seismically isolated buildings considering poundings

Abstract: Numerical simulations and parametric studies have been used to investigate the influence of potential poundings of seismically isolated buildings with adjacent structures on the effectiveness of seismic isolation. Poundings are assumed to occur at the isolation level between the seismically isolated building and the surrounding moat wall. After assessing some common force-based impact models, a variation of the linear viscoelastic impact model is proposed to avoid tensile impact forces during detachment, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
128
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 23 publications
0
128
0
1
Order By: Relevance
“…the impact stiffness and impact damping coefficients is a common difficulty when using forced-based impact models and it is often considered one of the major disadvantages of this method. Nevertheless, several numerical studies in 2D showed that in the case of simulating the problem of earthquake induced pounding of adjacent buildings, the values of the impact parameters slightly affect the overall structural response, besides of the acceleration at the impacting floor [9]. In the frames of the current study, a simple approximation is followed in order to determine a reasonable value for the impact stiffness and impact damping in both normal and tangential directions of the contact plane.…”
Section: Impact Stiffness Coefficientsmentioning
confidence: 98%
See 1 more Smart Citation
“…the impact stiffness and impact damping coefficients is a common difficulty when using forced-based impact models and it is often considered one of the major disadvantages of this method. Nevertheless, several numerical studies in 2D showed that in the case of simulating the problem of earthquake induced pounding of adjacent buildings, the values of the impact parameters slightly affect the overall structural response, besides of the acceleration at the impacting floor [9]. In the frames of the current study, a simple approximation is followed in order to determine a reasonable value for the impact stiffness and impact damping in both normal and tangential directions of the contact plane.…”
Section: Impact Stiffness Coefficientsmentioning
confidence: 98%
“…The results from the various 2D parametric studies have demonstrated the detrimental effects of pounding on the dynamic response of multistory buildings and showed the importance of this problem regarding the safety and functionality of these structures. Studies have also revealed the consequences of structural pounding on the dynamic response of seismically isolated buildings, which exhibit quite different dynamic characteristics from fixed-supported buildings [9][10][11]. Actually in the case of seismically isolated buildings the problem of the amplification of the response due to pounding is considered to be more serious since it is more likely to have more demanding performance requirements and higher expectations than for conventionally fixed-supported buildings.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental test by using different balls was carried out by Jankowski et al [13,14] and shown the effect of body material to impact velocity. Komodromos [15], Ye et al [16] and Yu and Gonzalez [17], Naderpour et al [18] have mathematically described various equations to determine impact damping ratio.…”
Section: Introductionmentioning
confidence: 99%
“…They coordinated a stereo-mechanical model with energy loss during the impact. Komodromos et al (2007) expressed an equation of motion to create an impact between two bodies, which could estimate the impact damping ratio. The base isolation systems have recently been described by Polycarpou (2011, 2012) and the pounding was numerically investigated.…”
Section: Introductionmentioning
confidence: 99%